2009
DOI: 10.1111/j.1440-1746.2008.05757.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma nitric oxide, L‐arginine, and arginase‐1 in cirrhotic patients with progressive renal dysfunction

Abstract: Worsening renal function in decompensated cirrhosis is accompanied by progressive elevation in plasma NOx and L-Arg. These findings support the hypothesis that NO-mediated vasodilation is probably linked with the mechanism of progressive renal failure in decompensated cirrhotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…In a study conducted by Kayali et al, NO levels were found to be increased in cirrhotic patients with renal dysfunction, and the highest levels were observed in patients with HRS. One of the notable findings in this study was the fact that L-arginine levels were increased in these patients [16]. …”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted by Kayali et al, NO levels were found to be increased in cirrhotic patients with renal dysfunction, and the highest levels were observed in patients with HRS. One of the notable findings in this study was the fact that L-arginine levels were increased in these patients [16]. …”
Section: Discussionmentioning
confidence: 98%
“…Plasma arginine concentrations were measured using an isotope-dilution gas chromatograph/mass spectrometry (GC/MS) method as previously described [16]. …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a patient with liver cirrhosis and hepatocellular carcinoma without any other risk factors has been reported (Tsang et al 2012). Variable degrees of hepatic cirrhosis also occur in other UCDs (LaBrecque et al 1979;Mori et al 2002), and increased levels of l-arginine have been observed in patients with liver cirrhosis with progressive loss of renal function (Kayali et al 2009). …”
Section: Clinical Characteristicsmentioning
confidence: 97%